Planificación de ingreso y salida de bienes patrimoniales y su relación con la gestión patrimonial en la UGEL Requena, 2020 - Pereyra Ampuero, David German (2022)
The general objective of the research study was to determine the relationship between the planning of entry and exit of heritage assets and asset management in the UGEL de Requena, 2020, where the correlational descriptive type and non-experimental design were used, made up of a population of 18 workers, the same ones who were surveyed through a questionnaire for data collection. Concluding that the planning of entry and exit of heritage assets is regular (22%), this is due to various shortcomings since the personnel in charge of the inventory always specify the regulations that govern their work, in turn, since they rarely they establish an inventory commission to carry out the physical inventory; as well, the standards for the control of the characteristics of the goods are almost never established. Regarding asset management, it is qualified as regular (22%), this is because they are in total disagreement with non-inventoriable assets, they are also undecided with the valuation of assets, however, they are in total agreement with the reorganization of missing goods, and in total disagreement with the reorganization of surplus goods. Finally, it was determined that there is a significant relationship between Planning of income and outputs of heritage assets and Asset Management, which was corroborated by a coefficient of 0.891 (considerable positive) and a bilateral significance of (0.000).